The Roles of Skin Fibroblasts at Local Acupoints in Chrono-Acupuncture - Nannan Liu; Zhengyu Zhao; Qizhi Zhou; Xiaohong Zhang; Yu Wang; Shiqi Huang; Dingjun Cai (Pain Research and Management)
Objective. The aim of this study was to demonstrate the peripheral mechanisms of chrono-acupuncture by observing acupuncture at different time points affecting relative proteins to regulate the cytoskeleton of fibroblasts differently. Methods. A total of 108 male SD rats (180–220 g) that have basic pain threshold within 3–10 s were selected and randomly divided into group A (n = 72) and control group (n = 36). After the succession of modeling with CFA injection, the rats in group A were randomly divided into model group and acupuncture group, each group containing 36 rats. Then according to the different treatment time, each group was randomly classified into 6 subgroups (ZT0, ZT4, ZT8, ZT12, ZT16, and ZT20), each subgroup containing 6 rats (n = 6). On the second day of successful modeling, the rats in the acupuncture group received acupuncture treatment at the corresponding time point, while the control group and the model group were only tied up at the corresponding time point without any treatments. Methods of operation: use 0.5-inch needles, puncture the rats’ “Zusanli” on the affected limb, with Twirling manipulation for a minute after every five minutes; the treatment lasts thirty minutes in total. After 7 days of treatments, the skin and subcutaneous tissue of rats’ acupoint area of “Zusanli” on the affected limb were taken and then stained by immunofluorescence double staining method to observe the expression of the fibroblast cytoskeleton F-actin and β-tubulin under the LSCM while using western blot to observe the expression of P38MAPK/P-P38MAPK. Results. The expression of the cytoskeleton F-actin and β-tubulin at acupoint area in the acupuncture group was significantly higher than that in the control and model group. The effect of acupuncture on the restructure of the fibroblast cytoskeleton is different at different time points, the most effective time point was at ZT12 while the least at ZT16. Acupuncture can decrease the high expression of P-P38MAPK/P38MAPK in the model group, and the effect has time differences. The expression of P-P38MAPK/P38MAPK increased more significantly at ZT16 than ZT12. Conclusion. The remodeling difference of fibroblast cytoskeleton after receiving acupuncture treatment could be one of the peripheral bases of the chrono-acupuncture.